Improved Human Mesenchymal Stem Cell Isolation. Issue 4 (May 2014) - Chan, Tzu-Min; Harn, Horng-Jyh; Lin, Hui-Ping; Chou, Pei-Wen; Chen, Julia Yi-Ru; Ho, Tsung-Jung; Chiou, Tzyy-Wen; Chuang, Hong-Meng; Chiu, Shao-Chih; Chen, Yen-Chung; Yen, Ssu-Yin; Huang, Mao-Hsuan; et al.
Human mesenchymal stem cells (hMSCs) are currently available for a range of applications and benefits and have become a good material for regenerative medicine, tissue engineering, and disease therapy. Before ex vivo expansion, isolation and characterization of primary hMSCs from peripheral tissues are key steps for obtaining adequate materials for clinical application. The proportion of peripheral stem cells is very low in surrounding tissues and organs; thus the recovery ratio will be a limiting factor. In this review, we summarized current common methods used to isolate peripheral stem cells, as well as the new insights revealed to improve the quantity of stem cells and their stemness. These strategies offer alternative ways to acquire hMSCs in a convenient and/or effective manner, which is important for clinical treatments. Improved isolation and mass amplification of the hMSCs while ensuring their stemness and quantity will be an important step for clinical use. Enlarged suitable hMSCs are more clinically applicable for therapeutic transplants and may help people live longer and better.